BK Virus and Transplantation - Carla Prezioso; Valeria Pietropaolo (Viruses, 2021)
As guest editors, we are pleased to present this Special Issue on BK virus (BKV) and transplantation with the intention of exploring some aspects related to BKV-associated diseases in transplant recipients, since they are still unclear [...]